'Our membership doesn't reflect the industry': the challenges of organising disability support workers. (2nd October 2017) - Douglas, Karen
ABSTRACT: Mobilisation theory seeks to explain how workers and trade unions are able to shift workplace grievances to forms of collective action. Drawing on mobilisation theory, the focus here is on two unions whose memberships include disability support workers in the not-for-profit disability support sector. Historically, union practice formed around servicing members in traditional workplaces. The introduction of neoliberal marketisation practices in the care sector in the 1990s diminished a workforce already the subject of institutional gender discrimination, low pay, poor working conditions, work undervaluation and weakened bargaining opportunities. How unions can identify and utilise opportunities to organise these workers continues to present significant challenges. Union strategy and tactics are examined to understand how vulnerable workers can be organised in an increasingly precarious and marketised environment.